EDUKASI MENCUCI TANGAN PADA PEDAGANG DAGING BABI DI PASAR KASIH NAIKOTEN, KOTA KUPANG, NTT - Nancy D. F. K. Foeh; Yeremia Yobelanno Sitompul; Diana Agustiani Wuri; Larry R. W. Toha (Jurnal Media Tropika, 2021)
The aim of this community service activity was to provide educational information related to the rules of the correct and good steps for washing hands. This activity was the one of simple procedure steps to break the chain of covid 19. This service activity was carried out with one of the pork traders at Kasih Traditional market, Naikoten, Kupang City, East Nusa Tenggara. The level of understanding of pork traders regarding the correct way of washing hands according to WHO (World Health Organization) standards is proven to increase understanding and knowledge after direct educational outreach activities which are measured by questionnaires before and after service activity.